THE USE WITHOUT RIGHT OF THE PRIVILEGED INFORMATION (INSIDE TRADING) – OFFENSE REGARDING THE CAPITAL MARKET - Mirela GORUNESCU (Challenges of the Knowledge Society)
This study addresses the particularly complex problem caused by one of the offense that can be committed in the capital market. Naturally, the article also includes an introductory analysis of the field and the regulation of the capital market, aspects that complement the premise of all offenses defined by the Law no. 297/2004, but examines in particular one of the incrimination texts regulated by the same normative act. It is about article 279 paragraph b) and article 245 of the Law no. 297/2004 which, without having a marginal designation, was intended to define the offense of unlawful use of the privileged information.